Impact of hypoglycaemia on patient-reported outcomes from a global, 24-country study of 27, 585 people with type 1 and insulin-treated type 2 diabetes. (August 2017) - Khunti, Kamlesh; Alsifri, Saud; Aronson, Ronnie; Cigrovski Berković, Maja; Enters-Weijnen, Catherine; Forsén, Tom; Galstyan, Gagik; Geelhoed-Duijvestijn, Petronella; Goldfracht, Margalit; Gydesen, Helge; Kapur, Rahul; Lalic, Nebojsa; et al.
Highlights: Hypoglycaemia has a major impact on patients' daily lives and diabetes management. There are large regional variations in patients' response to hypoglycaemia. Patient education programmes need to place greater emphasis on the avoidance and management of hypoglycaemic events. Abstract: Aims: Data on the impact of hypoglycaemia on patients' daily lives and diabetes self-management, particularly in developing countries, are lacking. The aim of this study was to assess fear of, and responses to, hypoglycaemia experienced by patients globally. Materials and methods: This non-interventional, multicentre, 4-week prospective study using self-assessment questionnaires and patient diaries consisted of 27, 585 patients, ≥18 years, with type 1 diabetes ( n  = 8022) or type 2 diabetes ( n  = 19, 563) treated with insulin for >12 months, at 2004 sites in 24 countries worldwide. Results: Increased blood glucose monitoring (69.7%) and seeking medical assistance (62.0%) were the most common responses in the 4 weeks following hypoglycaemic events for patients with type 1 diabetes and type 2 diabetes, respectively. Approximately 44% of patients with type 1 diabetes or type 2 diabetes increased calorie intake in response to a hypoglycaemic episode. Following hypoglycaemia, 3.9% (type 1 diabetes) and 6.2% (type 2 diabetes) of patients took leave from work or study. Regional differences in fear of, and responses to, hypoglycaemia were evident – in particular, a lower level of hypoglycaemic fear and utilisation of healthcare resources in Northern Europe and Canada. Conclusions: Hypoglycaemia has a major impact on patients and their behaviour. These global data for the first time reveal regional variations in response to hypoglycaemia and highlight the importance of patient education and management strategies.